Improving the Quality of Higher Education: Autonomy of State-Owned Universities - Sharifi, Mohammad Shafi (Journal of Social Sciences - Kabul University, 2022)
Over the past four decades, economic and technological developments, along with political and security challenges, have highlighted the significance and benefits of university autonomy. This study examines the issue of autonomy in state-governed universities in Afghanistan by drawing on international experiences and gathering the perspectives of university professors. The research follows a descriptive survey methodology, with the sample consisting of faculty members from eight leading public universities. Data were collected through an online survey and analyzed using SPSS software. The results indicate that the majority of professors, with slight variations, support university independence in financial, academic, institutional, and employment matters. Furthermore, open-ended responses suggest that greater autonomy enhances teaching quality, competitiveness, and scientific research within universities.